An analysis of cervical non-infectious inflammatory myelitis risk factors. (February 2014) - Zhou, Heng; Zhang, Xinghu; Bian, Liheng; Wang, Liqun; Wang, Yongjun; Zhao, Xingquan
Abstract : Background: Non-infectious inflammatory myelitis or non-infectious myelitis (NIM) is an inflammatory condition that occurs following an immune response in the central nervous system (CNS). In cases of spinal disc degeneration, multiple factors converge to cause pathologic changes in disc structure. To date, no studies have examined the potential relationship between disc degeneration and NIM. Objectives: To investigate the relationship between cervical NIM and cervical disc degeneration. Methods: Magnetic resonance imaging (MRI) was used to examine 85 patients with cervical NIM. Peripheral levels of the pro-inflammatory cytokines, interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-alpha) were also measured. Non-infectious myelitis occurrence rates and TNF-alpha and IL-6 levels were compared between patients with cervical disc degeneration and a control group. The relationship between cervical NIM and cervical disc degeneration was analyzed with logistic regression and a receiver operating characteristic (ROC) curve. Results: Magnetic resonance imaging showed that 78·8% of patients with myelitis exhibited disc degeneration compared to only 18·9% of the control group. Moreover, IL-6 and TNF-alpha levels in patients with NIM were significantly higher than those in the control group; levels of these inflammatory cytokines were even higher in NIM patients with cervical disc degeneration than in those without. Conclusions: Our results suggest that patients with cervical NIM have a higher incidence of cervical disc degeneration, indicating that cervical disc degeneration is likely a possible risk factor in cervical NIM progression. Future quantitative studies are required to confirm this observation.